Application of Spritz Encryption in Smart Meters to Protect Consumer Data - Kiarie, Lincoln Kamau; Langat, Philip Kibet; Muriithi, Christopher Maina (Journal of Computer Networks and Communications, 2019)
The ongoing upgrade of the electrical power system into a more powerful system known as Smart Grid has both benefits and costs. Smart Grid relies on advanced communication and hence offers better services through improved monitoring, planning, and control. However, enhanced communications make Smart Grid more susceptible to privacy leaks and cyber attacks. Small meters collect detailed consumer data, such as power consumption, which can then become a major source of privacy leakage. Encryption can help protect consumer data, but great care is needed. The popular RC4 (Rivest Cipher 4) encryption has been implemented in the widely deployed smart meter standard—Open Smart Grid Protocol (OSGP)—but has been shown to have major weaknesses. This paper proposes the use of Spritz encryption. Spritz is an RC4-like algorithm designed to repair weak design decisions in RC4 to improve security. A test on performing one encryption took only 0.85 milliseconds, showing that it is fast enough not to affect the operations of a smart meter. Its ability to withstand brute force attacks on small keys is also significantly greater than RC4’s ability.